2022
DOI: 10.1039/d2lc00428c
|View full text |Cite
|
Sign up to set email alerts
|

Ceiling culture chip reveals dynamic lipid droplet transport during adipocyte dedifferentiation via actin remodeling

Abstract: Adipocyte dedifferentiation has recently gained attention as a process underpinning adipocyte plasticity; however, a lack of suitable experimental platforms has hampered studies into the underlying mechanisms. Here, we developed a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…and TAZ regulation and pathways, 23,24,31 we can say that the confirmed expression of YAP in DFATs in our results (Fig. 2C) links the cell attachment and adhesion with the dedifferentiation process.…”
Section: Biomaterials Science Papersupporting
confidence: 77%
See 4 more Smart Citations
“…and TAZ regulation and pathways, 23,24,31 we can say that the confirmed expression of YAP in DFATs in our results (Fig. 2C) links the cell attachment and adhesion with the dedifferentiation process.…”
Section: Biomaterials Science Papersupporting
confidence: 77%
“…23,26,27 In the microfluidic system demonstrated by Kim et al, which provides the opportunity to observe the dedifferentiation mechanism in detail, it has been shown that actin myofibrils reorganize the cytoskeleton of the actin myofibrils and expel the lipid droplet from the cell, making the cells acquire a fibroblastic morphology while turning into DFATs. 24 This study also showed that coating with fibronectin on the surface promotes adipocyte dedifferentiation. Based on the related literature, we aimed to further control and improve the dedifferentiation ratio of mature adipocytes by using cationic and anionic polymers, and proteins which are the main components of the tissue extracellular matrix (ECM) and basement membrane (BM).…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations